2016
DOI: 10.5830/cvja-2016-014
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in the relationship between fatty liver disease and atherosclerosis

Abstract: SummaryBackgroundCarotid intima–media thickness (CIMT) is a surrogate of subclinical atherosclerosis. Fatty liver disease is also linked to increased risk of cardiovascular events. The aim of this study was to evaluate the association between fatty liver disease and CIMT according to gender.MethodsPatients who had undergone carotid and abdominal ultrasound between June 2011 and December 2013 were retrospectively evaluated. The differences between the CIMT values measured in the common carotid artery and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
2
9
0
1
Order By: Relevance
“…In male participants, we did not get a statistically significant result of two above association, which might be explained by a presumption that the negative effect of NAFLD such as MS, IR, dyslipidemia and so on is more significant in women than in man. This result was confirmed by a recent study that suggested that fatty liver disease was a useful predictor of atherosclerosis especially for female 35 . The gender differences in association between NAFLD and CAC or increased risk level of CHD need be further investigated.…”
Section: Discussionsupporting
confidence: 75%
“…In male participants, we did not get a statistically significant result of two above association, which might be explained by a presumption that the negative effect of NAFLD such as MS, IR, dyslipidemia and so on is more significant in women than in man. This result was confirmed by a recent study that suggested that fatty liver disease was a useful predictor of atherosclerosis especially for female 35 . The gender differences in association between NAFLD and CAC or increased risk level of CHD need be further investigated.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, Kim et al studied the association of atherosclerotic disease in FLD in relation to gender differences and concluded that males had a higher prevalence of FLD, carotid plaque and increased CIMT values compared to females (87). Martinez-Alvarado Mdel et al suggested that IR could be a mediator of metabolic abnormalities and subclinical atherosclerosis in females (88).…”
Section: Cardiovascular Disease In Fatty Liver Diseasementioning
confidence: 99%
“…[11][12][13] In a study examining the relationship between liver fat and gender, the rate of steatohepatitis and serum AST, ALT and GGT levels were found to be higher in men than in women. [14] Considering these findings, it should be clarified what is the reason for the higher AST and ALT levels in male patients in the present study; whether it is a gender-based change or a metabolic differentiation triggered after SG.…”
Section: Discussionmentioning
confidence: 75%